Effect of Aligning Forces by Two Preadjusted Edgewise Techniques on a Buccally Positioned Maxillary Canine at Varying Vertical Displacements: A Finite Element Study - Steve Mathew; Puneet Batra; Nitin Arora; Ashish Kumar Singh; Sridhar Kannan; Aditya Talwar (Galenos Yayinevi, 2024)
Objective: To evaluate the effect of continuous arch and piggyback mechanics in a straight wire appliance (SWA) for the alignment of buccal and variably vertically positioned maxillary canines. Methods: A three-dimensional finite element model with near-normal occlusion and buccal and vertically displaced maxillary canines was used. Two groups were created to simulate two commonly used SWAs techniques, continuous archwire (Group 1) and piggyback models (Group 2). Each group had three subgroups with varying vertical displacement of the canine from 2 to 6 mm from the occlusal plane. The displacement and stress distribution were noted in each group. Results: As the vertical displacement increased in Group 1, the concentration of von Mises stress increased progressively at the incisal third (0.36, 0.41 and 0.44 MPa) at 2, 4, and 6 mm, respectively, with decreased maximum occlusal movement in the vertical plane with respect to the canine. Group 2 exhibited a similar pattern but greater occlusal movement of the canine compared with Group 1. Conclusion: A vertical displacement of 4 mm is the optimal level at which continuous arch mechanics should be considered. For displacements beyond 4 mm, the piggyback wire technique is a suitable alternative.